A Method of developing the management of sport clubs to ensure the success of the sport professionalism system in Algeria - layachi.salem,; sedira.saad, (sports creativity, 2025)
The study aims to know the role of the method of developing the management of sports clubs in the success of the system of sports professionalism in Algeria, and in this study the descriptive method was used on a survey sample of 60 employees From the board of directors of professional sports clubs, we used a questionnaire listed in the form of the Triple Likert scale as a tool for collecting information The most important results of the study indicated that both (the degree of conformity of the objectives of the management of sports clubs and the degree of response of the organizational structures at the level of club management as well as the strategies adopted for club management) contribute to the success of the sports professional system in Algeria.